2021
DOI: 10.1108/ijcst-05-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Investigating facemask problems associated with wearing comfort and fit

Abstract: PurposeA facemask is used to cover the nose and mouth to protect a wearer's health in daily life. The authors’ long-term goal aimed to ensure more people with different physical characteristics and different attitudes can wear a high performance and comfortable facemask. In the present paper, wearers were surveyed by a questionnaire. Additionally, a prototype improvement pattern with a fit performance was investigated.Design/methodology/approachThe survey of facemask wearers was conducted with local students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The present results were supported by the research study conducted by Matt C. Howard and reported that, "Men were significantly more likely to perceive face masks as infringing upon their independence" [32] . An another study reported that, "the odds of an individual wearing a mask increased significantly with age and was also 1.5x greater for females than males" [32][33][34][35][36] . 4: Showing the attitude of facemask wearing in context of rural and urban participant.…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…The present results were supported by the research study conducted by Matt C. Howard and reported that, "Men were significantly more likely to perceive face masks as infringing upon their independence" [32] . An another study reported that, "the odds of an individual wearing a mask increased significantly with age and was also 1.5x greater for females than males" [32][33][34][35][36] . 4: Showing the attitude of facemask wearing in context of rural and urban participant.…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…Earlier studies have investigated the design of masks for fitting the closed mouths of younger Japanese men and women 1 and the open mouths of men. 2 Moreover, the design of comfortable masks has been studied for a female Japanese dummy with a closed mouth 3 and five young Japanese women with open mouths 4 in pilot studies. In addition, in a related survey 5 of university students in Japan (men, N = 1147, mean age of 19.8 years; women, N = 2050, mean age of 19.6 years) on attitudes toward wearing a mask, the percentage of respondents wearing a mask in daily life was higher in women (75.4%) than in men (48.2%).…”
mentioning
confidence: 99%